Anti-Corruption Education from an Early Age in Preventive Efforts Corruption Act - Rolib Sitorus; Elvina Tanoto (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
Anti-corruption education is one of the important discussions in the development of the state in Indonesia today, so in relation to this, the purpose of this study is to determine the factors that influence the success of anti-corruption education in the family environment, for the role of parents in instilling anti-corruption values ​​in children from an early age, and to determine an effective education model to be applied in the family in order to form an anti-corruption character in children. This study uses a qualitative descriptive method. The results achieved are that anti-corruption education in the family environment is an important foundation in forming the character of individuals with integrity. The success of this effort is greatly influenced by various interrelated factors. Overall, the success of anti-corruption education in the family environment is the result of a complex interaction between internal and external factors. To achieve optimal results, integrated efforts are needed from all parties, including parents, schools, and the community. Anti-corruption education in the family is an important foundation in building the character of children with integrity.